Analytical model for heterogeneous crystallization kinetics of spherical glass particles - Ferreira, Eduardo Bellini [UNESP]; Lopez-Richard, Victor; Zanotto, Edgar Dutra; Marques, Gilmar Eugenio (My University, 2009)
An analytical model developed to describe the crystallization kinetics of spherical glass particles has been derived in this work. A continuous phase transition from three-dimensional (3D)-like to 1D-like crystal growth has been considered and a procedure for the quantitative evaluation of the critical time for this 3D-1D transition is proposed. This model also allows straightforward determination of the density of surface nucleation sites on glass powders using differential scanning calorimetry data obtained under different thermal conditions. © 2009 The American Ceramic Society.
Keywords: Analytical model; Continuous phase transitions; Critical time; Glass Powder; Heterogeneous crystallization; Quantitative evaluation; Spherical glass; Surface nucleation; Thermal condition; Three-dimensional (3D); Crystallization kinetics; Differential scanning calorimetry; Glass; Grain boundaries; Models; Phase transitions; Three dimensional